Is it time to use checklists in mental health care auditing? - Jacob Polackiewicz; Alexander Grinshpoon; Moshe Z. Abramowitz (Mental Illness)
A key strategy for improving the quality of mental health care is the design and implementation of a mechanism for on-site inspection and clinical auditing. We discuss the use of checklists in auditing providing an objective, comprehensive system for recording and analyzing multi-disciplinary, clinical auditing in mental health services. We believe such an approach can identify potential risks and allow for better decision making.